Analisis Faktor Pencapaian Indikator Kapitasi Berbasis Pemenuhan Komitmen Pelayanan (KBPKP) di Puskesmas Kota Palembang - Siti Halimatul Munawarah; Misnaniarti Misnaniarti; Isnurhadi Isnurhadi (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
The Achievement of the CIBFSC indicator target in Public Health Center of Palembang City can be said to be not optimal because most of Public Health Center have not received 100% capitation payments because they cannot meet the three service commitment indicators. As many as 63% of Public Health Center  that do not meet CN indicators; 44% of Public Health Center did not meet the RPPRV indicators and 5% of Public Health Center did not meet the NSRR indicator (KCU Health BPJS Palembang, 2018). The purpose of this research was to analyze the Achievement Factors for Capitation Indicators Based on Fulfillment of Service Commitments (CIBFSC) in Public Health Center of Palembang City. The type of research used was quantitative research with cross sectional study. This research was a population sampling or total sampling, which was 41 CIBFSC Public Health Center program holders in Palembang City. The instruments used in this research included questionnaires, interviews, and observations with bivariate analysis. The results of this research showed that transmission (p = 0,000); clarity (p = 0.007); consistency (p = 0,000); commitment (p = 0,000); incentives (p = 0.056), SOP (p = 0.001); fragmentation (p = 0,000). Keyword : Achievement, CIBFSC, Public Health Center